Front Cover: Non‐classical Non‐covalent σ‐Hole Interactions in Protein Structure and Function: Concepts for Potential Protein Engineering Applications (Chem. Asian J. 7/2023). Issue 7 (6th March 2023) - Walker, Margaret G.; Mendez, C. Gustavo; Ho, P. Shing
Abstract : The σ‐hole theory describes the anisotropic distribution of electrostatic potential of organic substituents that participate in a broad range of nonclassical noncovalent ( nc NC) interactions found in chemistry and biochemistry. This review explores how halogen bonds, chalcogen bonds and tetrel bonds can affect the structures, assemblies, and potential functions of peptides and proteins. These three types of nc NC interactions have energies that are comparable to the H‐bond and, therefore, serve as important concepts in molecular recognition and potential tools for biomolecular design. More information can be found in the Review by P. Shing Ho et al.